Energy-dispersive x-ray microanalysis of elements’ content and antimicrobial properties of Pereskia bleo and Goniothalamus umbrosus - Abdelwahab, Siddig Ibrahim; Mohd Ain, Nooraini; Abdul, Ahmad Bustamam; Taha, Manal Mohamed Elhassan; Tengku Ibrahim, Tengku Azmi (Academic Journals, 2009)
This study was designed to investigate elements’ content and anti-microbial effects of two Malaysian plants, Pereskia bleo and Goniothalamus umbrosus. Elements’ analysis was carried out using Energy Dispersive X-ray Microanalysis combined with Variable Pressure Scanning Electron Microscope (EDX, VPSEM). Anti-microbial screening was performed using disc diffusion method using two gram-positive bacteria, methicillin resistant Staphylococcus aureus (MRSA) and Bacillus subtilis B29, and other two gram-negative bacteria, Pseudomonas aeruginosa60690 and Salmonella choleraesuis. The elemental distribution revealed the presence of C, O, Mg, P, S, Cl, K, Ca, Al, Si and Fe, in these medicinal plants and their relative weight percentages were estimated. A variable susceptibility of microbial strains of this study towards Pereskia bleo and Goniothalamus umbrosuswas noticeably observed. From this study, it is shown that the analysis of elements of anticancer plants can be considered as potential sources for providing information regarding the medicinal usages of plants.